Vitamin K3 (menadione) suppresses epithelial-mesenchymal-transition and Wnt signaling pathway in human colorectal cancer cells. (25th August 2019) - Kishore, Chandra; Sundaram, Sandhya; Karunagaran, Devarajan
Abstract: Tumor recurrence and metastasis decrease the survival rate of colorectal cancer (CRC) patients. Menadione reduces the numbers and incidences of 1, 2-dimethylhydrazine induced colon tumors in mouse but the mechanism of anticancer activity of menadione in colorectal cancer is not very clear. Since Wnt signaling is constitutively active in CRC and it aggravates the epithelial mesenchymal transition (EMT), the regulation of EMT and Wnt signaling by menadione (vitamin K3) was investigated in CRC cells. Menadione showed cytotoxicity against human CRC cells (SW480 and SW620) and human primary colon cancer cells but was relatively ineffective against the cells from human normal colon (CRL-1790) and human primary colon epithelial cells. Menadione suppressed invasion, migration and epithelial-mesenchymal transition in human CRC cells by upregulating the expression of E-cadherin (CDH1), ZO-1 and downregulating that of N-cadherin (CDH2), Vimentin (VIM), ZEB1, MMP2 and MMP9. Menadione decreased TOPFlash/FOPFlash luciferase activity and expression of several downstream targets of Wnt signaling and coactivators such as β-catenin (CTNNB1), TCF7L2, Bcl9l, p300 (EP300) and cyclin D1 (CCND1) was suppressed. Menadione induced differentiation and increased apoptotic cell population in SubG0 phase of cell cycle in SW480 and SW620 cells. The ability of menadione to suppress EMT, migration, invasion, Wnt signaling, cell proliferation and induce Sub G0 arrest, highlights its potential to be considered for intensive preclinical and clinical investigation in CRC. Highlights: Menadione is cytotoxic to colorectal cancer cells but not against normal cells. Menadione suppresses Wnt and EMT pathways in colorectal cancer cells. Menadione inhibits migration and invasion in colorectal cancer cells. Menadione arrests colorectal cancer cells in SubG0 phase of cell cycle. Menadione induces differentiation in colorectal cancer cells.